Developing AI-Based Teaching Materials with Solar System Scope for Elementary Education - Saputra, Mistaf Agung; Suratmi; Susiloningsih , Esti (IJE : Interdisciplinary Journal of Education, 2025)
The development of teaching materials based on Artificial Intelligence assisted by the Solar System Scope application for the solar system topic in Grade VI at SDN 05 Indralaya uses the ADDIE model. It aims to develop teaching materials on the solar system topic by achieving valid and practical levels of the developed materials. Data were collected through interviews, observations, documentation, and questionnaires. The research results show that the material validity reached 97.22%, categorized as very valid, and the media validity reached 95%, also categorized as very valid. The assessment from the trial of the developed teaching materials obtained an average of 95.5%, falling into the very valid category. The high scores from expert evaluations and trials indicate that the developed teaching materials are feasible and can be applied in school learning.